El programa de Ciencias Médicas Odontológicas y de la Salud del Posgrado General de la UNAM (2011 a 2023). - Fortoul van der Goes, Teresa I.; Manzanarez Villegas, Aleithia; Ochoa Cabrera, Alba; Castillo Sosa, Yahalí; Silva Méndez, Magnolia; Martínez Zúñiga, Aída; Estrada Nieves, Ana María; Morales Sánchez, Eduardo (Revista de la Facultad de Medicina de la UNAM)
By reviewing the scientific literature specialized in sleep disorders (TS) carried out in Mexico, especially at the TS Clinic (Faculty of Medicine-UNAM) at the General Hospital of Mexico (CTS-HGM) from 1948 to 2020, it was possible to document the history of ST research in Mexico and the role played by the CTS-HGM. Sleep Medicine (MS) is one of the newest specialties in Mexico and case research in this field began around 1948, while formal research in 1974. The founding of CTS-HGM in 1997 led to significant development in TS research in Mexico. In addition, the CTS-HGM became a center of care for patients with these problems, as well as important research center since its publications cover all the diagnostic categories of the CITS.